Environmental monitoring of waterborne Campylobacter: evaluation of the Australian standard and a hybrid extraction-free MPN-PCR method - Henry, Rebekah; Schang, Christelle; Chandrasena, Gayani I.; Deletic, Ana; Edmunds, Mark; Jovanovic, Dusan; Kolotelo, Peter; Schmidt, Jonathan; Williamson, Richard; McCarthy, David (Frontiers in Microbiology, 2015)
Campylobacter is the leading agent of diarrheal disease worldwide. This study evaluates a novel culture-PCR hybrid (MPN-PCR) assay for the rapid enumeration of Campylobacter spp. from estuarine and wastewater systems. To first evaluate the current, culture-based, Australian standard, an inter-laboratory study was conducted on 69 subsampled water samples. The proposed Most-Probable Number (MPN)-PCR method was then evaluated, by analysing 147 estuarine samples collected over a 2 year period. Data for 14 different biological, hydrological and climatic parameters were also collated to identify pathogen-environment relationships and assess the potential for method specific bias. The results demonstrated that the intra-laboratory performance of the MPN-PCR was superior to that of AS/NZS (σ = 0.7912, P<0.001; κ = 0.701, P<0.001) with an overall diagnostic accuracy of 94%. Furthermore, the analysis of both MPN-PCR and AS/NZS identified the potential for the introduction of method specific bias during assessment of the effects of environmental parameters on Campylobacter spp. numbers.